GIS and Street View Integration: Analyzing Spatial Factors of Motorcycle Taxi Stands in Bangkok - Wirat Rattanapitak; Phatthanan Sirikitsathian (My University, 2024)
Motorcycle taxis play a vital role in addressing lastmile connectivity challenges in Bangkok’s complex urban transportation system. However, the factors influencing the spatial distribution of these informal transport services remain poorly understood. Kernel Density Estimation (KDE) was employed to examine the spatial distribution patterns, revealing two primary high-density clusters of stands in southern Chatuchak. Proximity analysis quantified relationships between the 208 stand locations and urban infrastructure factors, finding strategic positioning near mass transit stations (avg. 1.79 km), on sidewalks (70.5%), and in mixed-use areas with predominantly residential (33.19%) and commercial (29.32%) land use within a 100m radius. A decision tree model identified residential area proportion (importance 0.3423) and distance from metro stations (0.2935) as key predictors of stand presence, but achieved moderate accuracy (52.38%). The results highlight the close integration of motorcycle taxi stands within the urban fabric and their role in enhancing accessibility.
Keywords: Urban Transport and Accessibility; Transportation and Mobility Innovations; Urban and Freight Transport Logistics